POLITIK HUKUM PEMBENTUKAN PERATURAN PEMBATASAN TERHADAP ANAK YANG MENYAKSIKAN TAYANGAN BIOSKOP DENGAN RATING DEWASA DITINJAU DARI PERSPEKTIF HAM - Nadia Junesti; Emilda Firdaus; Widia Edorita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
Along with the development of entertainment technology, people have many alternativechoices where to look for entertainment, especially films. The cinema is a democratic public space,whoever has the right to come to access the screen that is currently playing. Even though not allfilms that are produced can be watched by all groups, because there are many contents that are notsuitable to watch, especially for children. However, there are cinema entrepreneurs who allowchildren to access shows with content not intended for children. Talking about human rights, itcannot be separated from children's rights. Regarding the rights and obligations of children wecan see in the Child Protection Law, namely Article 4 to Article 10 of Law No. 35 of 2014concerning amendments to Law No. 23 of 2002 on Child Protection. So in this case there areinherent and unavoidable children's rights. So that parents, society, and the State are expected tobe able to protect a child, because children are a gift as the nation's successor. The behavior of achild whether the child will become the future of the nation depends on the education provided byparents, society and the State.This study uses a typology of normative legal research or what is also called doctrinallegal research, which specifically discusses the level of legal synchronization, because it is relatedto the legal politics of the formation of restrictions on children who watch cinema shows with adultratings from a human rights perspective.The results of the research conducted by the author are, Basically the politics ofregulation regarding cinema, every film shown, circulated, or shown in the cinema must passcensorship. Passing this sensor is evidenced by the existence of a sensor pass certificate. A passcertificate is issued by the Film Censorship Institute (LSF) and signed by the Chairman of the LSF.There are no explicit rules prohibiting cinemas from allowing minors to buy tickets or watch filmswith an "adult" rating. What exists is the sanctions imposed by the LSF for film business actors (inthis case cinema entrepreneurs) who neglect the provisions concerning the inclusion of ageclassification of film viewers. Based on Article 8 paragraph (2) letter d jo. Article 55 of theBroadcasting Law, the sanctions that can be given are limited in nature, namely only limited tosanctions for violating regulations and broadcasting code of conduct as well as broadcast programstandards broadcast by broadcasting institutions that provide broadcasting services both radio andtelevision. So in this case the LSF does not have the authority to impose sanctions on parents orcinemas who allow children to watch cinemas with adult ratings.Keywords: Cinema- Political Law- Human Rights